The holiday makers : understanding the impact of leisure and travel - Krippendorf, Jost (Heinemann, 1987)
Analyses the different forms of tourism, examines the effects on the indigenous countries and their people, and outlines positive steps to reconcile people's holiday requirements with the world's economic and social structures.